A systemic approach to the reconstruction of engineering structures using intelligent information systems and regulatory-technical frameworks - Stepaniuk, R. (Ways to Improve Construction Efficiency, 2022)
The article substantiates the relevance of implementing intelligent information systems (IIS) in the processes of engineering structure reconstruction as an important vector of digital transformation in the construction industry. Contemporary challenges — including the technical aging of critical infrastructure, a high degree of structural wear, and increasing requirements for reliability, resilience, and energy efficiency — necessitate the adoption of a comprehensive approach to managing reconstruction activities. The study demonstrates that reconstruction is impossible without the preliminary stages of technical monitoring, inspection, and residual life assessment of structures, as prescribed by current regulatory documents: DSTU-N B V.1.2-18:2016, DBN V.1.2-14:2018, and DBN A.3.1-5:2016. These documents clearly define the necessity of integrating technical condition evaluation into the general reconstruction cycle. The article proposes a systemic classification of engineering structures based on functional purpose, which serves as a foundation for further technological modeling of their reconstruction in accordance with the regulatory and legal framework. A synthesis of international experience and analytical forecasts (including McKinsey and ABC) demonstrates that without digitalization and large-scale workforce retraining, the construction sector will be unable to adequately respond to growing challenges. Therefore, the use of IIS in reconstruction processes is not seen as an optional innovation, but as an essential tool to ensure the reliability, safety, and technological compliance of engineering structures under modern conditions. The implementation of IIS — particularly BIM/CIM modeling, automated control systems, machine learning algorithms, digital sensors, and common data environment (CDE) platforms — enables more efficient decision-making, improves the accuracy of reconstruction solutions, and reduces costs at all stages. IIS are actively applied during inspection, design, construction execution, and post-reconstruction monitoring, ensuring continuity of information flows, timely risk response, efficient logistics, and long-term operational performance of structures.